Change in Visceral Adiposity Independently Predicts a Greater Risk of Developing Type 2 Diabetes Over 10 Years in Japanese Americans - Wander, Pandora L. (American Diabetes Association, 2013)
OBJECTIVE: —Visceral adiposity is an important risk factor for cardiovascular disease and type 2 diabetes. We sought to determine whether change in intraabdominal fat area (IAF) over time predicts subsequent development of diabetes. RESEARCH DESIGN AND METHODS: —We followed up 436 nondiabetic Japanese-American subjects (mean age 51.9 years, mean BMI 24.2 kg/m(2), 54% male) for development of diabetes. We fit a logistic regression model to examine the association over a 10-year follow-up between change in IAF at 5-year follow-up and other fat areas (measured by computed tomography) and development of incident diabetes, adjusted for age, sex, family history of diabetes in a first-degree relative, second-generation versus third-generation Japanese American (Nisei vs. Sansei), baseline IAF, BMI, weight change over time, smoking status, physical activity level, and subcutaneous fat (SCF) depot areas. RESULTS: —Cumulative incidence of diabetes was 20.4% at 10 years. Mean change in IAF was 10.9 cm(2). An increase of 1 SD in IAF was associated with a 1.65-fold increase in the odds of diabetes over 10 years (OR = 1.65, 95% CI 1.21–2.25) after adjusting for the above covariates. This association was also independent of changes in thoracic, thigh, and abdominal SCF, as well as change in weight. CONCLUSIONS: —We conclude that baseline IAF and accumulation of fat in this area over time are independent predictors of the development of type 2 diabetes in Japanese Americans.